New Aliphatic Alcoholic Acid Constituent from the Roots of Panax ginseng - Chung, Ill-Min; Kim, Seung-Hyun; Ahmad, Ateeque (Asian Journal of Chemistry, 2013)
One new constituent 14a,15a,16a,17a,18a,19a,20a,21a-octahydroxy-16,17,18-trimethyl-n-triacontan-trans,trans-22,24-dien-1-oic acid was isolated and identified from the methanol extract of heat processed roots of Panax ginseng. The structure of compound was elucidated with the help of 600 MHz by 1D and 2D NMR (COSY, HSQC, HMBC) spectroscopic techniques aided by FAB MS and IR spectra.